Search for B → K(*)[nu][nu][bar] and invisible quarkonium decays - Lees, Jean-Pierre; Adametz, Aleksandra; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2013)
We search for the flavor-changing neutral-current decays B→K(*)ν¯ν, and the invisible decays J/ψ→ν¯ν and ψ(2S)→ν¯ν via B→K(*)J/ψ and B→K(*)ψ(2S), respectively, using a data sample of 471×106 B¯¯¯B pairs collected by the BABAR experiment. We fully reconstruct the hadronic decay of one of the B mesons in the Υ(4S)→B¯¯¯B decay, and search for the B→K(*)ν¯ν decay in the rest of the event. We observe no significant excess of signal decays over background and report branching fraction upper limits of B(B+→K+ν¯ν)<3.7×10−5, B(B0→K0ν¯ν)<8.1×10−5, B(B+→K*+ν¯ν)<11.6×10−5, B(B0→K*0ν¯ν)<9.3×10−5, and combined upper limits of B(B→Kν¯ν)<3.2×10−5 and B(B→K∗ν¯ν)<7.9×10−5, all at the 90% confidence level. For the invisible quarkonium decays, we report branching fraction upper limits of B(J/ψ→ν¯ν)<3.9×10−3 and B(ψ(2S)→ν¯ν)<15.5×10−3 at the 90% confidence level. Using the improved kinematic resolution achieved from hadronic reconstruction, we also provide partial branching fraction limits for the B→K(*)ν¯ν decays over the full kinematic spectrum.
Im Titel sind die runden Klammern "()" und das Sternchen "*" hochgestellt
Im Titel ist "Ny" (bzw. "nu") als griechischer Buchstabe dargestellt
Im Titel steht der zweite griechische Buchstabe "Ny" (bzw. "nu") mit einem Oberstrich
Gesehen am 17.11.2021